2012
DOI: 10.1016/j.ajog.2012.08.007
|View full text |Cite
|
Sign up to set email alerts
|

Is polycystic ovary syndrome another risk factor for venous thromboembolism? United States, 2003–2008

Abstract: OBJECTIVE-We sought to determine prevalence and likelihood of venous thromboembolism (VTE) among women with and without polycystic ovary syndrome (PCOS). STUDY DESIGN-We performed a cross-sectional analysis using Thomson Reuters MarketScanCommercial databases for the years 2003 through 2008. The association between VTE and PCOS among women aged 18-45 years was assessed using age-stratified multivariable logistic regression models.RESULTS-Prevalence of VTE per 100,000 was 374.2 for PCOS women and 193.8 for wome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(42 citation statements)
references
References 37 publications
2
35
0
5
Order By: Relevance
“…Furthermore, our finding of a doubling of the incidence of venous thrombosis among women with PCOS has recently been confirmed in a study in the United States of women with PCOS taking the oral contraceptive pill (OCP) and a 50% increased risk in women with PCOS not taking the OCP (38). An earlier study had demonstrated the increased risk of venous thrombosis for women with PCOS, and reported a potential beneficial effect when a woman with PCOS was commenced on the OCP (39). Furthermore, in line with previous literature (40), we noted an excess of cerebrovascular events and arterial disease in women with PCOS, which is a significant concern considering the young age of this PCOS population, suggesting that intervention to address any coexistent adverse lifestyle features is essential.…”
Section: Cardiometabolic and Thrombotic Healthsupporting
confidence: 72%
“…Furthermore, our finding of a doubling of the incidence of venous thrombosis among women with PCOS has recently been confirmed in a study in the United States of women with PCOS taking the oral contraceptive pill (OCP) and a 50% increased risk in women with PCOS not taking the OCP (38). An earlier study had demonstrated the increased risk of venous thrombosis for women with PCOS, and reported a potential beneficial effect when a woman with PCOS was commenced on the OCP (39). Furthermore, in line with previous literature (40), we noted an excess of cerebrovascular events and arterial disease in women with PCOS, which is a significant concern considering the young age of this PCOS population, suggesting that intervention to address any coexistent adverse lifestyle features is essential.…”
Section: Cardiometabolic and Thrombotic Healthsupporting
confidence: 72%
“…Among women aged 18 -24 with PCOS the adjusted odds ratio for VTE was 3.26 (95% CI, 2.61 -4.08) [20]. In another population-based cohort study examining VTE risk among women with PCOS who were not using hormonal contraception the relative risk of VTE compared to non PCOS subjects was 1.…”
Section: Polycystic Ovary Syndromementioning
confidence: 99%
“…Доведено, що в пацієнток із СПКЯ ризик венозних тром-боемболічних ускладнень є значно вищим, ніж загалом у популяції [54][55][56]. Так, у масштабному дослідженні за участю 90 тис.…”
Section: інструментальні обстеженняunclassified
“…Так, у масштабному дослідженні за участю 90 тис. пацієнток у США було виявлено, що часто-та венозних тромбоемболій у жінок із СПКЯ на 60% вища, ніж у контрольній групі (відносний ризик 1,6; 95% довірчий інтервал 1,13-2,34) [54]. Поряд із іншими порушеннями об-міну речовин схильність до тромбоутворення при СПКЯ також обумовлена гіперінсулінемією, що стимулює синтез інгібітора активатора плазміногену-1 (маркера тромбозів), який в свою чергу пригнічує фібриноліз [39,57].…”
Section: інструментальні обстеженняunclassified